Kajian Analisa Arsitektur Ekologi Responsif Udara pada Kawasan Penginapan - Kurnia Devi, Ida Ayu Viyanthi; Laskara, Gede Windu (Jurnal Arsitektur Universitas Udayana, 2022)
The development that is now carried out massively is intended as a response to the needs of the community for housing or as a goal in advancing the standard of living. In fact, the development has an adverse impact on the environment, such as the use of energy and natural resources that are not exposed to disfifected and polluted. The dominant use of energy is found in buildings with residential functions that utilize electrical energy as a source of energy for the destruction and construction of buildings. This is because the factor that causes discomfort in the building is the hot air. Based on this background, the need for the application of ecological architecture concept in residential buildings (inns). The case study on the Crystal Dome – Amethyst, New Earth Haven Lodge building aims to analyze the application of designs and materials that support the concept of air responsive ecological architecture. The method used is qualitative descriptive that analyzes the use of the principle of air responsive ecological architecture. It is expected that by applying the concept of environmentally sensitive ecology in the new earth haven lodge area can make the environment maintained ecosystem by minimizing the adverse impact on the environment. The result of this study is the principle of air responsive ecology, among others by regulating the orientation of buildings, adjusting the orientation of cross ventilation, landscape elements (vegetation) and natural materials. So that the temperature in the building can be maintained in comfortable conditions and does not require the use of mechanical equipment.